2017
DOI: 10.1136/bmjqs-2017-006699
|View full text |Cite
|
Sign up to set email alerts
|

Precommitting to choose wisely about low-value services: a stepped wedge cluster randomised trial

Abstract: NCT02247050; Pre-results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(55 citation statements)
references
References 51 publications
1
53
0
Order By: Relevance
“…As Table 1 shows, the other categories were much less common. For instance, we found only five studies that facilitated commitment (Casper, 2008;Erasmus et al, 2010;Kullgren et al, 2018;Meeker et al, 2014;Verbiest et al, 2014). A detailed description of all the interventions by category can be found in the files for this article uploaded to the JBPA Dataverse.…”
Section: Nudges and Targeted Outcomesmentioning
confidence: 99%
See 2 more Smart Citations
“…As Table 1 shows, the other categories were much less common. For instance, we found only five studies that facilitated commitment (Casper, 2008;Erasmus et al, 2010;Kullgren et al, 2018;Meeker et al, 2014;Verbiest et al, 2014). A detailed description of all the interventions by category can be found in the files for this article uploaded to the JBPA Dataverse.…”
Section: Nudges and Targeted Outcomesmentioning
confidence: 99%
“…The categories with the highest percentages of positive outcomes were changing option-related efforts (88% of studies reported success, for instance Chan et al, 2013), providing social reference points (71%, for instance Hong, Ching, Fung & Seto, 1990), and using a combination of nudges (76%, for instance Hulgan et al, 2004). The categories with the highest percentages of mixed outcomes were facilitating commitment (40%, for instance Kullgren, Krupka, Schachter & Linden, 2018) and changing choice defaults (22%, for instance Ansher et al, 2014). Change option consequences had the highest percentage of null outcomes (50%, for instance Beidas et al, 2017), followed by translating information (44%, for instance Jousimaa et al, 2002).…”
Section: Success Of Nudges By Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…A second reason that robust evaluation is needed is that these issues may be trickier to gain traction on than might be anticipated. For example, Kullgren et al ’s recent study of the impact of clinicians’ precommitting to follow Choosing Wisely recommendations with decision supports showed only a small, unsustained decrease in potentially low-value activity for one of three targeted conditions and a small increase in alternative orders 29. This is an interesting example as seeking to draw on the behavioural economics strategy of precommitment (committing one’s future self to a course of action) makes intuitive sense given its apparent success in changing other behaviours.…”
Section: Insights From Healthcare Improvement Researchmentioning
confidence: 99%
“…Although discussing costs in medicine may be more taboo compared with purchasing a car, home, or other good, renewed governmental pushes for pricing transparency make having awareness of what services provide "good bang for the buck" an essential skill. 5,6,9,10,12 This review highlights how we define and measure cost-effective care, how key inputs are incorporated into decision-making evidence synthesis, and how policy makers model a clinical situation to optimize cost-effective care delivery. To help better understand some of the terminology used in this primer, a glossary of terms is provided in Table 1.…”
Section: Introductionmentioning
confidence: 99%